Combined use of bulked segregant analysis and microarrays reveals SNP markers pinpointing a major QTL for resistance to Phytophthora capsici in pepper - Wing -Yee, Lui; Kang, J.H.; Seok Jeong, H.; Choi, H.J.; Yang, H.; Kim, K.; Choi, D.; Choi, G.J.; Jahn, M.; Kang, B.C. (Springer, 2014)
Pkytophthora capsici L. is one of the most destructive pathogens of pepper (Capsicum spp.). Resist ance of pepper against P. capsici is controlled by quantitative trait loci (QlL), including a major Q1L on chromo some 5 that is the predominant contributor to resistance. Here, to maximize the effect of this QlL and study its underlying genes, an F2 population and recombinant inbred lines were inoculated with P. capsici strain JHAil-7 zoospores at a low concentration (3 x 103 phenotype segregation ratios for the populations fit a 3:1 and 1:1 (resistant:susceptible) segregation model, respectively, consistent with a single dominant gene model. Bulked segregant analysis (BSA) using Affymetrix Gene Chips revealed a single position polymorphism (SPP) marker mapping to the major QlL. When this SPP marker (Phyto5SAR) together with other SNP markers located on chromosome 5 was used to confirm the position of the major QlL, Phyto5SAR showed the highest WD value at the Q1L. A scaffold sequence (scaffold194) containing Phyto5SAR was identified from the C. annuum genome database. The scaffold contained two putative NBS-LRR genes and one SAR 8.2A gene as candidates for contributing to P. capsici resistance. Markers linked to these genes were developed and validated by testing 100 F1 commercial cultivars. Among the markers, Phyto5NBS1 showed about 90 % accuracy in predicting resistance phenotypes to a low-virulence P. capsici isolate. These results suggest that Phyto5NBS1 is a reliable marker for P. capsici resistance and can be used for identification of a gene(s) underlying the major Q1L on chromosome 5.